Wiskott-Aldrich Syndrome protein is required for homeostasis and function of invariant NKT cells - Astrakhan, Alexander (2009)
NKT cells comprise a separate T lineage expressing semi-invariant T cell receptors. Canonical iNKT cells specifically recognize lipid antigens presented by CD1d, a MHC Class I-like molecule. iNKT cells function, in part, as initial responders to bacterial infection and play a role in immune surveillance and tumor rejection. The Wiskott-Aldrich Syndrome protein (WASp) serves as a crucial link between cellular stimuli and cytoskeletal rearrangements. While we and others have identified a key role for WASp in homeostasis of T-regulatory and marginal zone B cells, little data exist regarding the role for WASp within the iNKT lineage. Analysis of WASp-expressing cell populations in heterozygous female WASp mice revealed a substantial selective advantage for WASp(+) vs. WASp(− )iNKT cells. While adult WASp-deficient (WASp(−/−)) mice had normal thymic and BM iNKT numbers, we observed 2–3 fold reduction in the numbers of iNKT cells in the spleen and liver. This peripheral iNKT deficit is manifested, in part, due to defective iNKT homeostasis. WASp(−/− )iNKT cells exhibited reduced levels of integrin surface expression and decreased homing and/or retention within peripheral tissues in a competitive repopulation model. In addition, analysis of young mice showed that WASp is important for both maturation and egress of thymic iNKT cells. WASp(−/− )iNKT cells also exhibited a marked reduction in antigen-induced proliferation and cytokine production. Our findings highlight the crucial role for WASp in iNKT development, homeostasis and activation, and identify iNKT dysfunction as an additional factor likely to contribute to the clinical features observed in WAS patients.